Zona baja de Belén - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1974)
SPANISH: panoramic view of the Itaya River in the lower part of Belen, next to an improvised wooden stairway and houses.
ENGLISH: vista panoramica del rio itaya zona baja de Belén junto a una escalinata improvisada de madera y casas.

SPANISH: panoramic view of the Itaya River in the lower part of Belen, next to an improvised wooden stairway and houses.
ENGLISH: vista panoramica del rio itaya zona baja de Belén junto a una escalinata improvisada de madera y casas.
Lower Bethlehem area
Keywords: Iquitos (Perú)|~|Iquitos antiguo|~|Perú--Cultura|~|Perú--Patrimonio Cultural